Children's play in diverse cultures (SUNY series, children's play in society, 1994)
"This book illuminates play as a universal and culture-specific activity. It provides needed information about the behavior of children in diverse cultural contexts as well as about the play of children in unassimilated cultural or subcultural contexts. It offers readers the opportunity to develop greater sensitivity to and better understanding of the important cultural differences that confront early childhood teachers and teacher educators."--BOOK JACKET.